2016
DOI: 10.3390/toxics4040028
|View full text |Cite
|
Sign up to set email alerts
|

Haematological, Biochemical and Antioxidant Changes in Wistar Rats Exposed to Dichlorvos Based Insecticide Formulation Used in Southeast Nigeria

Abstract: Abstract:The indiscriminate use of pesticide is a treat to non-target organisms. This study evaluates the haematological and biochemical changes induced by inhalation of local Nigerian dichlorvos insecticide on rats. The rats were randomly assigned to a control group which received only food and water and a test group which, in addition to food and water, was exposed to the pesticide for a period of 4 h daily for 28 days, after which exposure was discontinued for seven days. Five animals were sacrificed from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 18 publications
8
31
3
1
Order By: Relevance
“…The reduced levels of RBC, HGB, and PCV reported in this study, following DDVP exposure, suggested the hematotoxic effects of DDVP. This was in accordance with a previous study [19] and was strengthened by the reports concerning exposure to other OPs [13,20,21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reduced levels of RBC, HGB, and PCV reported in this study, following DDVP exposure, suggested the hematotoxic effects of DDVP. This was in accordance with a previous study [19] and was strengthened by the reports concerning exposure to other OPs [13,20,21].…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in MCV and MCH with an increase in MCHC that we observed, were similar to previous researches [13,19], but it was in disagreement with the report that claimed an undisturbed erythrocytes indices after exposure to OP [22]. Also, the changes in total WBC, neutrophils, and lymphocytes documented in this study were in where strengthened with the reports of previous studies [13,14], with the exception of a reduction in lymphocyte count [13].…”
Section: Discussioncontrasting
confidence: 58%
“…ACT treated mice showed normocytic normochromic anemia as their MCV (mean corpuscular volume), MCH (mean corpuscular hemoglobin content) and MCHC (mean corpuscular concentration in hemoglobin) values did not significantly differ from controls ( Table ). Our findings were similar to previous researches using different types of xenobiotics, and were reinforced by many reports concerning acetamiprid exposure …”
Section: Resultssupporting
confidence: 92%
“…This indicated that the overriding potential of MSKE to improve the PCV value could not affect the MSG-induced effect on the PCV value of the rats. Increased PCV value suggested potential increase in RBC production or erythropoiesis resulting to polycythaemia [47,48,51,62,63] as noted in this study; decreased thrombotic events or cardiovascular mortality [50] ; higher protection on the integrity of erythrocytes by boosting their volume percentage in the blood [50] ; improved transport of oxygen and absorbed nutrients [28,30] . The PCV value of the control in this study compared with that in earlier studies [48,62] .…”
Section: Discussionmentioning
confidence: 86%
“…Increased RBC count suggested potential stimulation of erythropoietin releases from the kidneys with a resultant increase in RBC synthesis (erythropoiesis) or diminished destruction that could result to polycythemia (instead of anema) and enhanced oxygencarrying/delivery capacity via the blood in the rats [28,36,37,[47][48][49] . This further indicated higher MSKE- related benefit and protection on the hematology of the rats [47,[49][50][51] . However, the higher but nonsignificant (p>0.05) RBC count in the rats exposed to MSG alone or to MSG plus low MSKE groups compared to the control indicated that MSG at the tested concentration either alone or together with low MSKE concentration did not cause measureable destruction of matured RBC's or change in the rate of production of RBCs (erythropoiesis) due probably to inability to stimulate erythropoietin (the humoral regulator of RBC production) release in the kidney [52] .…”
Section: Discussionmentioning
confidence: 98%